The Relationship Between Organizational Behavior and Functional Performance: Perspectives from Financial Management, Human Resources, and Marketing - Burhanuddin, Burhanuddin (Abadi Institute, 2024)
This research aims to analyze the influence of organizational behavior on functional performance in financial management, human resources, and marketing. Organizational behavior encompasses aspects such as motivation, leadership, communication, and job satisfaction that can affect functional performance in various management fields. The research method used is literature study and descriptive analysis. The results of the study indicate that organizational behavior has a significant influence on functional performance in financial management, human resources, and marketing. The implications of this research emphasize the importance for organizations to pay attention to and enhance organizational behavior in order to achieve optimal functional performance.